Monocarboxylate Transporter 4 Triggered Cell Pyroptosis to Aggravate Intestinal Inflammation in Inflammatory Bowel Disease - Wang, Yaodong; Zhou, Xiaorong; Zou, Kejian; Chen, Guanhua; Huang, Ling; Yang, Fangying; Pan, Wenxu; Xu, Hongwei; Xu, Zhaohui; Chen, Huan; Chen, Jiayu; Gong, Sitang; et al. (Frontiers in Immunology, 2021)
NLRP3 inflammasome has emerged as a crucial regulator of inflammatory bowel disease (IBD) characterized by a chronic inflammatory disease of the gastrointestinal tract. The expression of MCT4 is significantly increased in intestinal mucosal tissue of IBD, which has been identified to regulate intestinal barrier function. However, the function of MCT4 in cell pyroptosis remained unknown. In this study, we have established a stable cell line with MCT4 overexpression in HT-29 and CaCO2 cells, respectively. Functional analysis revealed that ectopic expression of MCT4 in CaCO2 cells contributed to cell pyroptosis as evidenced by LDH assay, which is largely attributed to Caspase-1-mediated canonical pyroptosis, but not Caspase-4 and Caspase-5, leading to cleave pro-IL-1β and IL-18 into mature form and release mediated by cleaved GSDMD. Mechanically, MCT4 overexpression in HT-29 and CaCO2 cell triggered the phosphorylation of ERK1/2 and NF‐κB p65, while inhibition of MCT4 by MCT inhibitor α-Cyano-4-hydroxycinnamic acid (α-CHCA) in HT-29 and CaCO2 cells led to a significant downregulation of ERK1/2 and NF‐κB activity. What’s more, blockade of ERK1/2-NF‐κB pathway could reverse the promotion effect of MCT4 on IL-1β expression. Importantly, both MCT4 and Caspase-1, GSDMD were significantly increased in patients with IBD, and a positive clinical correlation between MCT4 and Caspase-1 expression were observed(p<0.001). Taken together, these findings suggested that MCT4 promoted Caspase-1-mediated canonical cell pyroptosis to aggravate intestinal inflammation in intestinal epithelial cells (IECs) through ERK1/2-NF‐κB pathway.